Esthiomene - Sarkar J; Sengupta B.N; Sharma M.K; Bhattacharya P; Barman M.K (Wolters Kluwer Medknow Publications, 1995)
A case of esthiomene with chroni inguinal lymphadenopathy, groove sign and multiple atrophic inguinal scars in a 40 year old woman is reported for its rare incidence these days.